DNA Methylation and Chromatin Remodeling: The Blueprint of Cancer Epigenetics - Dipanjan Bhattacharjee; Smita Shenoy; Kurady Laxminarayana Bairy (Scientifica)
Epigenetics deals with the interactions between genes and the immediate cellular environment. These interactions go a long way in shaping up each and every person’s individuality. Further, reversibility of epigenetic interactions may offer a dynamic control over the expression of various critical genes. Thus, tweaking the epigenetic machinery may help cause or cure diseases, especially cancer. Therefore, cancer epigenetics, especially at a molecular level, needs to be scrutinised closely, as it could potentially serve as the future pharmaceutical goldmine against neoplastic diseases. However, in view of its rapidly enlarging scope of application, it has become difficult to keep abreast of scientific information coming out of various epigenetic studies directed against cancer. Using this review, we have attempted to shed light on two of the most important mechanisms implicated in cancer, that is, DNA (deoxyribonucleic acid) methylation and histone modifications, and their place in cancer pathogenesis. Further, we have attempted to take stock of the new epigenetic drugs that have emerged onto the market as well as those in the pipeline that offer hope in mankind’s fight against cancer.